1996
DOI: 10.1074/jbc.271.40.24982
|View full text |Cite
|
Sign up to set email alerts
|

Murine α-Macroglobulins Demonstrate Divergent Activities as Neutralizers of Transforming Growth Factor-β and as Inducers of Nitric Oxide Synthesis

Abstract: Human ␣ 2 M induced NO synthesis comparably to m␣ 2 M; however, MUG had no effect. These studies demonstrate that the ability to neutralize TGF-␤ is a property of m␣ 2 M, which is not redundant in the murine ␣-macroglobulin family or in murine plasma. M␣ 2 M is the only murine ␣-macroglobulin that promotes NO synthesis. The absence of m␣ 2 M, in ␣ 2 M(؊/؊) mice, may allow TGF-␤ to more efficiently suppress excessive iNOS expression following endotoxin challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 55 publications
0
42
0
Order By: Relevance
“…In addition, iNOS from vascular endothelial cells appeared to produce a lower level of NO than that from macrophages. It has been reported that IFN-␥ in combination with LPS or TNF-␣ enhanced NO production in mouse vascular endothelial cells (4,25,29,34,35). However, the individual actions of IFN-␥, LPS, and TNF-␣ are not well-documented.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, iNOS from vascular endothelial cells appeared to produce a lower level of NO than that from macrophages. It has been reported that IFN-␥ in combination with LPS or TNF-␣ enhanced NO production in mouse vascular endothelial cells (4,25,29,34,35). However, the individual actions of IFN-␥, LPS, and TNF-␣ are not well-documented.…”
Section: Discussionmentioning
confidence: 98%
“…The activity of cNOS allows for constitutive low-level production of NO by unstimulated vascular endothelial cells and is thought to be fundamental for the maintenance of a nonthrombogenic surface and the inhibition of cell adhesion to the endothelium (22). Vascular endothelial cells stimulated with various agents (LPS, cytokines, and growth factors) begin to accumulate mRNA encoding iNOS several hours following agonist stimulation (4,25,29,34,35). NO produced by both cNOS and iNOS increases endothelial cell permeability, and the increased permeability allows the accumulation of growth factors necessary for stimulation of mitogenesis and tissue repair (22).…”
mentioning
confidence: 99%
“…This may also explain why platelets from control mice are unresponsive to exogenous TGF␤1. Plasma contains low levels of circulating, active TGF␤1 bound to carriers such as ␣-macroglobulin (41,42). The presence of the TGF␤1 carriers in the plasma of Scid Tgfb1 Ϫ/Ϫ mice may account for why a relatively large amount of TGF␤1 (20 ng/ml) was needed to improve aggregation responses of Scid Tgfb1 Ϫ/Ϫ platelets.…”
Section: Scid Tgfb1mentioning
confidence: 99%
“…In adult tissues, TGF-␤-binding proteins limit cytokine activity, thereby controlling tissue remodeling and inflammation. For example, TGF-␤ latency-associated peptide and ␣2-macroglobulin regulate inflammation and response to infection (24,25). ␣2-HS-glycoprotein (Ahsg)/ fetuin is a glycoprotein present in serum and extracellular matrix that binds to TGF-␤ cytokines (bone morphogenetic proteins 2, 4, and 6 and TGF-␤1 and TGF-␤2) via a 19 amino acid cytokine-binding domain homologous to an extracellular sequence in the T␤RII (26).…”
Section: Introductionmentioning
confidence: 99%